O livro didático e o enfoque cts: possibilidades para o estudo dos gases no ensino médio - Sousa, Ivanessa Castro de (2019)
The STS (Science-Technology-Society) studies represent a vast and complex branch of knowledge, with many thematic foci and that aggregates many researchers. The STS movement emerged in the United States, in college education, between the 1960s and 1970s. In Latin America, the origin of the STS discussions is found in the reflection of Science and Technology as a responsibility of public policies. The Latin American Thought About Science-Technology-Society emerges at the end of the 1960s as criticism of the situation of science and technology and of some aspects of state politics (VACCAREZZA, 1998). As the years went by, this focus has been gaining projection. With the objective to understand the role of the Chemistry textbook in the possibility of adoption of the STS approach to the concept of Study of Gases, the present work proposes the analysis, through a state of knowledge, of how the literature specialized in teaching treats the concepts related to the Study of Gases. In this perspective, it was performed a bibliographical research, from a systematic study with eleven periodicals chosen according to Qualis CAPES about the concept Study of Gases. With the data obtained from this systematic study, it was observed that, from the 20 articles found, 11 approached the concept. In their vast majority, the periodicals treated the concept in a manner directed to laboratory practices, with gaps being pointed out about the approach of this concepts in the periodicals analyzed. It was also performed an analysis of textbooks, with the goal to identify if those works presented STS approach in the concept Study of Gases. This analysis was performed in 6 high-school Chemistry textbooks that were approved by the National Textbook Program (PNLD), that were implemented in the schools in the academic year of 2018. The categories of analysis were reasoned with the assumptions of Bardin's Content Analysis (2011); furthermore, it was used, based in these criteria and fundamentals, Minayo (2002), Gil (2002), Marconi (2010), Ricardson et al. (2011). In this analysis, it was highlighted aspects a priori of philosophical, sociological, historical, political, economic and humanistic nature that characterize, according to Rosenthal (1989), the aspects related to Science in its broadest dimension for the contents of the STS curriculum. From this analysis, and considering that the work presented the STS approach, it was specified, through subcategories, which strands were characterized: the European, the North American or from the reflection of the Latin American Thought About Science-Technology-Society. It was also performed interview with five Chemistry teachers of the public school system, State and Federal, for identification of the teachers' thoughts about the STS interactions in the high-school Chemistry textbooks. In the content analysis of the interviews, it was noticed that the teachers identified the importance of the concept for the formation of students, its role in situations that occur in their daily lives. It was identified in the speech of many teachers the concern with approaching the concept as preparation for ENEM. Only one of the five teachers identified the importance and aspects of the STS interactions in the textbooks